2011
DOI: 10.1029/2011gc003877
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of subduction initiation with different evolutionary pathways

Abstract: [1] Changes of plate motion may have induced subduction initiation (SI), but the tectonic history of SI is different from one subduction zone to another. Izu-Bonin-Mariana (IBM) SI, accompanied by strong backarc spreading and voluminous eruption of Boninites, contrasts with the Aleutians which shows neither. Using finite element models, we explore visco-elasto-plastic parameters and driving boundary conditions for SI evolution. With an imposed velocity, we find three different evolutionary modes of SI: continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 35 publications
1
82
0
Order By: Relevance
“…Oceanic lithosphere on the South American side of the margin was thrust far enough beneath the Antarctic Peninsula and for long enough that subduction was forced to initiate (Leng and Gurnis, 2011). The loss of South American lithosphere in this way continued until segments of the South American-Antarctic mid-ocean ridge, approaching from southeast of the collision zone, started colliding with it in Miocene times.…”
Section: South American-antarctic Plate Divergencementioning
confidence: 93%
“…Oceanic lithosphere on the South American side of the margin was thrust far enough beneath the Antarctic Peninsula and for long enough that subduction was forced to initiate (Leng and Gurnis, 2011). The loss of South American lithosphere in this way continued until segments of the South American-Antarctic mid-ocean ridge, approaching from southeast of the collision zone, started colliding with it in Miocene times.…”
Section: South American-antarctic Plate Divergencementioning
confidence: 93%
“…(3) Spontaneous subduction involving the vertical sinking of older, denser lithosphere along a transform-fracture system, as proposed by many authors (e.g., Karig 1982;Stern and Bloomer 1992;Shervais and Choi 2011) can also be ruled out. First of all, reasonable numerical models indicate that compression across the boundary fault is required (e.g., Toth and Gurnis 1998;Gurnis et al 2004;Leng and Gurnis 2011;Leng et al 2012) and the classical mode of failure of lithosphere under compression is localization of the deformation along conjugated shear bands dipping at an angle of ∼50°, then failure along one of them and thrust development (e.g., Shemenda 1992). The theoretical conditions used in numerical models to initiate a "spontaneous" gravitational sinking lithosphere require an extremely young (newly formed) upper plate separated from an old, dense oceanic plate by a very weak boundary zone and sometimes even a no-slip condition on the down-going plate (Gerya et al 2008;Gerya 2012;Leng and Gurnis 2015).…”
Section: Possible Trigger For Psp Inceptionmentioning
confidence: 99%
“…Since the oldest lavas that include subduction components (near the KPRDaito Ridge intersection) are ∼48-49 Ma old (Ishizuka et al 2011a), we suppose that about 10 m.y. were necessary for the former transform boundary to turn into a subduction, as suggested by numerical models (Leng and Gurnis 2011;Leng et al 2012). At this stage, it is important to note that subduction did not initiate along a transform fault separating a younger and an older oceanic plate as has often been described (e.g., Shervais and Choi 2011;Stern et al 2012) but along a transform boundary between Mesozoic terranes characterized by a crust ∼20 km thick (Nishizawa et al 2014) and an oceanic plate characterized by a ∼6-7 km crust but with a lithosphere of highly variable thickness along the strike.…”
Section: Ibm Subduction Inceptionmentioning
confidence: 99%
“…Subduction initiation has been addressed primarily through numerical modeling (2)(3)(4)(5)(6)(7)(8)(9). These studies have demonstrated the need for a weak zone in the lithosphere to facilitate subduction.…”
mentioning
confidence: 99%